Etnoscience Study in Basic Science Course - I Nyoman Selamat; Luh Mitha Priyanka (Universitas Pendidikan Ganesha, 2023)
Learning difficulties experienced by students in basic science learning are basic science topics are still very textual. Students become confused and difficult to solve contextual problems. One way to link science topics through contextual learning is by integrating local wisdom into science content. One study related to local wisdom is ethnoscience. Ethnoscience is an attempt to reconstruct indigenous knowledge in society (indigenous science) into scientific knowledge (scientific knowledge). This reconstruction process will be useful in supporting the achievement of science concepts in learning. Therefore, it is considered important to research to identify the original scientific concepts in Balinese people which can be included in Basic Science learning. This research is qualitative research that aims to identify and analyze Balinese ethnoscience studies in Basic Science learning. The subjects of this research were students and expert lecturers who were taken through purposive sampling technique. Data on student learning difficulties were obtained through observation and interviews, while data on the relevance of Balinese ethnoscience studies in Basic Science learning were obtained through questionnaires, interviews, and literature studies. The results of this study indicate that there are Balinese ethnoscience studies in Basic Science learning, especially in separating mixtures, diversity of living things, heat, material changes, and biotechnology. With this result, basic science learning will be more contextual using Balinese ethnoscience study as an example. Furthermore, the difficulties in learning science experienced by students can be overcome. Keywords: contextual learning; ethnoscience; basic science